The influence of social media content on political identity with corruption perception as a moderator - Jia, Na; Fee, Lee Yok (Frontiers in Political Science, 2025)
Political identity is key to maintaining social cohesion and political stability. At present, when political apathy among Chinese youth prevails, the Chinese government regards social media as a significant threat to political identity. However, the impact of user-generated social media content on political identity has not been fully explored, especially in the context of epidemic corruption. This study examines how four dimensions of social media content, information sharing, building new relationships, self-presentation, and enjoyment, shape the political identity of Chinese university students, and how perceptions of corruption moderate these relationships in an authoritarian context. Data were collected through a simple random sample survey of 633 students and analyzed using structural equation modeling and hierarchical regression. Results show that information sharing, self-presentation, and enjoyment significantly strengthen political identity, whereas building new relationships has no direct effect. Moreover, corruption perception weakens the positive associations between social media content and political identity. By clarifying the differentiated effects of social media content and the contextual role of corruption, this study integrates Social Identity Theory and Relative Deprivation Theory into political identity research within an authoritarian context, offering new theoretical insights. Practically, the findings suggest that improving political transparency and tolerance can help unlock the positive potential of social media, fostering broader political identity and social cohesion.